A proposal for an open‐source financial risk model. Issue 3 (2014) - Jong Ho Hwang
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to present a policy proposal for building a new framework for gathering, measuring and disclosing financial risk information in the global economy. Design/methodology/approach – The paper examines the current state of the financial risk framework, notes its advantages and disadvantages and proposes a new construct that aims to address some of the shortcomings that are currently in place. The goals of a robust financial risk model are examined to determine the design of the proposed risk framework. Findings – The proposed open‐source financial risk model separates the dual function that internal risk models perform within financial institutions, first to attempt to optimize the risk–return profile of mostly private economic rent‐seeking entities, and second to maximize safety and soundness considerations for the public which is at risk of bearing the consequences of financial actors. Practical implications – The model allows widespread use of robust financial risk models. Social implications – The model enables a more transparent and democratic process for risk management. Originality/value – The study proposes a new global supervisory framework. Practical implications – The model allows widespread use of robust financial risk models. Social implications – The model enables a more transparent and democratic process for risk management. Originality/value – The study proposes a new global supervisory framework. <ack> <x xml:space="preserve"> Acknowledgements </x> The author is grateful to Richard Haynes, Timothy Karpoff, Tobias Adrian, John Connolly, Patty Kao, Kim Egert, Marc Joffe, Darrell Duffie, Oliver Chen, Simon Cheshire, Annette Heuser, Anat Admati, Hyun Song Shin, Jon Danielsson, Charles Taylor and the research team at the US Department of the Treasury's Office of Financial Research for their thoughtful comments, input and discussion. An earlier version of this work was published as a discussion paper of the Systemic Risk Centre at the London School of Economics. The commenters do not necessarily agree with the contents of this proposal. The views expressed here do not necessarily represent those of the US Department of the Treasury. Any errors contained in this paper are entirely those of the author. The author was formerly a large broker‐dealer risk supervisor at the US Securities and Exchange Commission. </ack>